Cytomegalovirus Retinitis Occurring as a Complication of HyperCVAD Chemotherapy: Report of Two Cases - Narayanan, Geetha; Haridas, Lakshmi; Soman, Lali V (Indian Journal of Medical and Paediatric Oncology, 2018)
Cytomegalovirus (CMV) retinitis is usually diagnosed in patients with acquired immunodeficiency syndrome and in solid organ and hematopoietic stem cell transplant recipients. It produces a characteristic necrotizing retinitis which is a sight-threatening condition in these patients. CMV retinitis occurs rarely in patients undergoing only chemotherapy, and very few cases have been reported during the maintenance phase of acute lymphoblastic leukemia (ALL) in children. We report two patients, one with ALL and the other with Burkitt’s lymphoma on HyperCVAD chemotherapy developing CMV retinitis during the course of treatment. Both patients were treated with intravenous ganciclovir, oral valganciclovir and intravitreal ganciclovir. Both patients are alive in remission at 60 and 40 months, respectively, with preservation of normal vision.
Keywords: Cytomegalovirus; HyperCVAD; retinitis